The Induction of systemic Resistance in plants by UsingPlant Growth Promoting Rhizobacteria ( PGPR) to control the root knot disease on tamato caused by Meloidogyne spp - Abdulridha, Estabraq M.; Abdulfattah, Farqad A. (Journal of Kerbala for Agricultural Sciences, 2016)
This study was conducted to determine the possibility of inducing a systemic resistance against the root knot disease caused by Meloidogyne spp. Two biological agents Pseudomonas fluorescens and Bacillus subtilis isolated from weeds in previous study were evaluated their efficiency separately or mixed in inducing the systemic resistance. The results showed that all treatments were able in reducing the penetration percentage of the second stage of Meloidogyne Larva to the roots of tomato plants comparing with the control. The biological mixture was the best with decreasing percentage reached 74.6% followed by P. fluorescens only with 71.2% and B. subtilis with 68.1%. Additionally, application of the biological factors in soil and rhizosphere of tomato plants was better than spaying them on the foliage of plants. As well as, the enzymatic parameters indicated to increase in activity of peroxide enzyme and accumulation of phenolic compounds in plants treated with the biological agents separately or mixed. The highest phenolic concentration was found in plants treated with the biological mixture followed by P. fluorescens only and B. subtilis only. Clearly, the data demonstrated that all treatments used in this study were able in inducing the systemic resistance in tomato plants against the root knot nematode and increasing of growth parameters thus it is encouraging in applied these biological agents particularly the mixture as biocide to control the root knot disease.